2000
DOI: 10.1084/jem.192.5.681
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of T Lymphocyte Costimulation with Cytotoxic T Lymphocyte–Associated Antigen 4–Immunoglobulin (Ctla4ig) Reverses the Cellular Pathology of Psoriatic Plaques, Including the Activation of Keratinocytes, Dendritic Cells, and Endothelial Cells

Abstract: Efficient T cell activation is dependent on the intimate contact between antigen-presenting cells (APCs) and T cells. The engagement of the B7 family of molecules on APCs with CD28 and CD152 (cytotoxic T lymphocyte–associated antigen 4 [CTLA-4]) receptors on T cells delivers costimulatory signal(s) important in T cell activation. We investigated the dependence of pathologic cellular activation in psoriatic plaques on B7-mediated T cell costimulation. Patients with psoriasis vulgaris received four intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
189
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 300 publications
(200 citation statements)
references
References 65 publications
(94 reference statements)
5
189
1
5
Order By: Relevance
“…In several studies, CD28 blockade has led to significant and clinically relevant modulation of inflammatory diseases (17)(18)(19)(20)(21)(22)(23)(24). Besides reduced T cell infiltration, some of these studies have reported a diminished tissue PMN Ϫ recruitment (19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several studies, CD28 blockade has led to significant and clinically relevant modulation of inflammatory diseases (17)(18)(19)(20)(21)(22)(23)(24). Besides reduced T cell infiltration, some of these studies have reported a diminished tissue PMN Ϫ recruitment (19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of bleomycin-induced lung fibrosis, CD28 gene-deficient mice demonstrated reduced concentrations of chemokines, which were crucial for leukocyte recruitment and activation (20). It is interesting that recent studies have revealed that CD28 blockade also seemed to reduce the infiltration of PMN into chronically inflamed tissues (19,20,23,24). Because these inflammatory diseases were not primarily PMN Ϫ dependent, it remains unknown whether T cells can modulate acute, PMN-dependent inflammatory syndromes and subsequent organ failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abatacept is an approved treatment for chronic inflammatory conditions such as rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA), in which T cells are involved in the pathophysiology of the disease (25)(26)(27)(28)(29)(30). In a phase I study of abatacept in patients with psoriasis vulgaris, clinical improvement was associated with a reduction of the intralesional T cell population (31,32). Taken together, these observations suggest that abatacept could be effective in the treatment of PsA.…”
mentioning
confidence: 99%
“…Reduction of epidermal hyperplasia correlating with a decrease in Tcell infiltrates and diminished epidermal proliferation were also observed. 114 No increase in T-cell apoptosis was identified in the skin lesions, suggesting that the decreased number of T cells was due to reduced proliferation and recruitment of T cells. CTLA-4Ig therapy did not induce long-term tolerance to T-cell dependent neoantigens.…”
Section: Co-stimulatory Blockade Treatments In Human Autoimmune Diseasesmentioning
confidence: 97%